American Colonists: From Deep Divisions to a Difficult Alliance - Kendouz,Ayoub; Cherifi, Akram Mohamed; Mihoubi,Ahmed (University of Ammar Theledji -Laghouat, 2020)
This dissertation is a study that explores the facts behind the colonies' alliance in Colonial America to revolt against the British Empire despite their tensions and past. This study attempts to reveal the key events that led to the American Revolution in each colony, as well as the key battles that won each colony its liberty. Thus, it aims to investigate the origins of these colonies by providing an overview of the immigrants that came to settle in the New World during the seventeenth and the eighteenth centuries. It compares the different cultures, religions, and lifestyles that they brought to America. Moreover, it aims to reveal the tensions between the settlers themselves and their expansion at the Native Indians' expense. The methodology adopted in this research is the narrative method which allowed the researchers to provide preliminary information on the background of immigration to Colonial America and the cultural and religious contrasts leading up to conflicts. The main conclusion drawn from this research is that not all the colonies revolted against the British Empire. The colonies that did were united in their decisions against the British oppression and approached it by votes of each colony‟s representatives; however, once the war started each colony fought its independence war separately